Morphometric and histological parameters in veins of diabetic patients undergoing brachiocephalic fistula placement. Issue 4 (2nd March 2015) - Lazich, Ivana; Chang, Anthony; Watson, Sydeaka; Dhar, Promila; Madhurapantula, Rama S.; Hammes, Mary
Abstract Diabetic patients with end‐stage renal failure have higher rates of arteriovenous failures when compared with nondiabetics. The aim was to compare differences in indicators of vascular remodeling and endothelial dysfunction in veins of patients with or without diabetes at the time of surgical placement. In this prospective observational trial, vein samples were collected from patients when a brachiocephalic fistula was created. Morphometric measurements and extent of fibrosis were determined using Image J software. Histological analysis, for the presence of myofibroblasts and level of endothelial nitric oxide synthase, was performed by immunohistochemical staining and scored in semi‐quantitative manner. Asymmetric dimethylarginine was determined at the time of access placement. Comparison of diabetics and nondiabetics was performed using Wilcoxon rank sum and Fisher's exact tests. Eighteen patients were included; 10 were diabetics. There was a significant difference in the measurement of vein area between groups, with diabetic vein samples having larger luminal area of average 832, 001.18 μm2 (317, 582.17–3, 695, 670.36, P = 0.04). The maximal intimal to medial thickness ratio was higher in diabetic vein samples (0.71 vs. 0.24, P = 0.03) along with statistically significant higher maximal intimal thickness (312.12 vs. 115.14 μm, P = 0.03). There is a significant difference in vascular wall remodeling between diabetics and nondiabetics at the level of the cephalic vein at the time of brachiocephalic placement. The unexpected finding of significantly larger luminal area in diabetic veins could be a major factor positively affecting brachiocephalic outcomes in otherwise impaired remodeling in this patient population.